Delivering safe and effective test-result communication, management and follow-up: a mixed-methods study protocol. Issue 2 (15th February 2018) - Dahm, Maria R; Georgiou, Andrew; Westbrook, Johanna I; Greenfield, David; Horvath, Andrea R; Wakefield, Denis; Li, Ling; Hillman, Ken; Bolton, Patrick; Brown, Anthony; Jones, Graham; Herkes, Robert; et al.
Abstract : Introduction: The failure to follow-up pathology and medical imaging test results poses patient-safety risks which threaten the effectiveness, quality and safety of patient care. The objective of this project is to: (1) improve the effectiveness and safety of test-result management through the establishment of clear governance processes of communication, responsibility and accountability; (2) harness health information technology (IT) to inform and monitor test-result management; (3) enhance the contribution of consumers to the establishment of safe and effective test-result management systems. Methods and analysis: This convergent mixed-methods project triangulates three multistage studies at seven adult hospitals and one paediatric hospital in Australia. Study 1 adopts qualitative research approaches including semistructured interviews, focus groups and ethnographic observations to gain a better understanding of test-result communication and management practices in hospitals, and to identify patient-safety risks which require quality-improvement interventions. Study 2 analyses linked sets of routinely collected healthcare data to examine critical test-result thresholds and test-result notification processes. A controlled before-and-after study across three emergency departments will measure the impact of interventions (including the use of IT) developed to improve the safety and quality of test-result communication and management processes. Study 3 adopts a consumer-driven approach, including semistructured interviews, and the convening of consumer-reference groups and community forums. The qualitative data will identify mechanisms to enhance the role of consumers in test-management governance processes, and inform the direction of the research and the interpretation of findings. Ethics and dissemination: Ethical approval has been granted by the South Eastern Sydney Local Health District Human Research Ethics Committee and Macquarie University. Findings will be disseminated in academic, industry and consumer journals, newsletters and conferences.